2002
DOI: 10.1093/nar/gkf442
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ribonuclease expression by estradiol in Rana catesbeiana (Bullfrog)

Abstract: Multiple ribonucleases are widely found in living organisms, but the function and regulation of individual ribonucleases are still not clear. In the present study, we found that one oocytic ribonuclease, RC-RNase, is developmentally expressed in the liver and stored in the oocyte of the bullfrog, while another ribonuclease, RC-RNase L1, is constitutively expressed and retained in the liver at all stages. In females, the expression of RC-RNase increased with the degree of maturity and the concentration of plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, what has not been explored at all is the role of these lectin-ribonucleases in vivo and their potential for host defense in their natural setting. Liao and colleagues [143] have shown that estrogen can control expression of these genes. Furthermore, multiple Rana sequences have evolved under positive selection pressure into multigene clusters [144,145], in a manner similar to that observed for the rodent eosinophil-associated ribonuclease genes [70].…”
Section: Rnase a Ribonucleases From The Bullfrog Rana Speciesmentioning
confidence: 99%
“…However, what has not been explored at all is the role of these lectin-ribonucleases in vivo and their potential for host defense in their natural setting. Liao and colleagues [143] have shown that estrogen can control expression of these genes. Furthermore, multiple Rana sequences have evolved under positive selection pressure into multigene clusters [144,145], in a manner similar to that observed for the rodent eosinophil-associated ribonuclease genes [70].…”
Section: Rnase a Ribonucleases From The Bullfrog Rana Speciesmentioning
confidence: 99%
“…It has been reported that cSBL acts as an anti-cancer agent against various human cancer cells including carcinoma (cervical, oral, hepatocellular, and breast), leukemia, lymphoma, mesothelioma, and glioblastoma [ 24 , 41 , 42 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Interestingly, although cSBL induces apoptosis in those cancer cells, normal tissue-derived cells, such as fibroblasts, melanocytes, keratinocytes, and mesothelial cells, are relatively insensitive to this agent [ 53 , 56 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%